Electrochemical bromination of organosulfur containing species for the determination of the strength of garlic (A. sativum) - Hall, EM; Tschulik, K; Batchelor-McAuley, C; Compton, RG (Elsevier, 2015)
The extraction by ethyl acetate and subsequent electrochemical detection of organosulfur containing molecules from garlic is demonstrated. The electrochemical results first evidence the high sensitivity of the process towards the model compound propyl disulfide. Through the in situ formation of bromine at a platinum electrode the propyl disulfide can be readily detected at concentrations as low as 12.5 μM. Second, the work focuses on the detection of organosulfur from fresh garlic samples. Extraction of the organosulfur ‘flavour’ molecules is achieved with ethyl acetate. Addition of this extract to the electrochemical cell results in an analytically useful signal allowing the voltammetric peak height to be successfully correlated with the garlic strength, as measured using an organoleptic tasting panel.